ANALYSIS OF QRIS USE AS A PAYMENT METHOD AT THE “X” EYE CLINIC IN SURABAYA - Asti Indriani; Djoko Pitoyo; Rahadian Malik; Ayu Laili Rahmiyati; Vip Paramarta; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Digital transformation in the healthcare sector has driven the adoption of a cashless payment system through the Quick Response Code Indonesian Standard (QRIS) to improve administrative efficiency and service quality. This study aims to analyze the effectiveness of QRIS implementation as a digital payment method at Eye Clinic X Surabaya and identify factors that support and hinder its implementation. The study used a qualitative approach with a case study design. Informants were purposively selected, consisting of one financial manager, four cashiers, and five QRIS patient users. Data were collected through in-depth interviews, observation, and documentation, then analyzed using thematic analysis assisted by NVivo 14 software. The results showed that QRIS implementation was able to improve the effectiveness of administrative services through faster, easier, more accurate, and more efficient transaction processes. The use of QRIS also helped reduce queues, simplify transaction recording, and increase patient convenience in making payments. However, implementation still faces several obstacles, including internet network instability, delays in transaction notifications, low digital literacy among some elderly patients, and suboptimal standard operating procedures (SOPs) and training for staff. Based on Campbell's effectiveness framework, QRIS implementation has met most of the organizational effectiveness indicators, although further strengthening of technological infrastructure, improving human resource competency, and organizational support are still needed for sustainable digital transformation. This research contributes to enriching the study of digital payment implementation in healthcare facilities, particularly at the clinic level, as a basis for developing policies and strategies for digital healthcare services in Indonesia.